The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m114.629519
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Calcium Exchanger 1 Regulates Epithelial Cell Migration via Calcium-dependent Extracellular Signal-regulated Kinase Signaling

Abstract: Background: Sodium-calcium exchanger (NCX1) regulates calcium in renal epithelial cells. Results: Na,K-ATPase ␤-subunit regulates NCX1 membrane localization and reduced NCX1 expression or its functional inhibition increases cell migration. Conclusion: NCX1 plays a pivotal role in activation of calcium dependent migration via calmodulin/PI3K/ERK. Significance: Identifying regulators of epithelial cell motility is important in establishing novel therapeutic targets in fibrosis and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Growing evidence supports the contribution of altered Ca 2+ signaling to tumor progression and metastasis, suggesting that agents targeting calcium influx and calcium influx-driven downstream signaling may hopefully offer alternative approaches for cancer therapy [17,18]. Several calcium channels blockers have been investigated in clinical trials [1921]; however, their efficacy has not been satisfactory for unclear reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports the contribution of altered Ca 2+ signaling to tumor progression and metastasis, suggesting that agents targeting calcium influx and calcium influx-driven downstream signaling may hopefully offer alternative approaches for cancer therapy [17,18]. Several calcium channels blockers have been investigated in clinical trials [1921]; however, their efficacy has not been satisfactory for unclear reasons.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting cooperation between the Na + /K + -ATPase and the Na + /Ca 2+ -exchanger in cell migration has been unveiled [98]. Stoichiometric efflux of 1 Ca 2+ ion in exchange for the uptake of 3 Na + ions is driven by the high Na + concentration in the extracellular medium and the membrane potential (negative inside) generated by the Na + /K + -ATPase.…”
Section: Calmodulin and Cell Migrationmentioning
confidence: 99%
“…Binding of the regulatory β-subunit of the ATPase to the Na + /Ca 2+ -exchanger inhibits its activity, which increases the [Ca 2+ ] cyt that in turn induces cell migration. This is due to the Ca 2+ /CaM-mediated activation of PI 3 K that activates the mitogen-activated protein kinase (MAPK) pathway resulting in the phosphorylation of myosin light-chain via myosin light-chain kinase (MLCK) and Rho-kinase (ROCK) [98] (see Figure 2).…”
Section: Calmodulin and Cell Migrationmentioning
confidence: 99%
“…We showed earlier that inhibition of NCX1 increases cell migration in kidney epithelial cells (13). Because enhanced migration is one of the characteristics acquired by carcinoma cells, we tested whether NCX1 expression is altered in renal cancers.…”
Section: Expression Of Ncx1 Mrna and Protein Is Down-regulated In Renmentioning
confidence: 98%
“…We showed earlier that functional inhibition of NCX1 led to enhanced cell migration in renal epithelial cells and that NCX1 interacts with adhesion protein, the ␤-subunit of Na,K-ATPase (13). Another study indicated that NCX1 was up-regulated during stroma-induced cell adhesion in the prostate epithelium (14).…”
mentioning
confidence: 95%